Mucosa-associated gut microbiome in Japanese patients with functional constipation - Inoue, Ryo; Inatomi, Osamu; Andoh, Akira; Morishima, So; Sugitani, Yoshihiko; Imai, Takayuki; Nishida, Atsushi; Kawahara, Masahiro; Naito, Yuji (Journal of Clinical Biochemistry and Nutrition, 2021)
The number of patients with chronic constipation is increasing in Japan. We investigated the gut mucosa-associated microbiome in Japanese patients with functional constipation. Diagnosis was made according to the Rome IV criteria. Mucosal samples were obtained by gentle brushing of mucosa surfaces. The gut microbiome was analyzed using 16S rRNA gene sequencing. There were no significant differences in bacteria α-diversity such as richness and evenness. The PCoA indicated significant structural differences between the constipation group and healthy controls (p = 0.017 for unweighted and p = 0.027 for weighted). The abundance of the phylum Bacteroidetes was significantly higher in the constipation group. The abundance of the genera Streptococcus, Fusobacterium, Comamonas, and Alistipes was significantly higher in the constipation group. The abundance of the genera Acinetobacter, Oscillospilla, Mucispirillum, Propinibacterium, and Anaerotruncus was significantly lower in the constipation group. In the constipation group, the proportion of genes responsible for sulfur metabolism, selenocompound metabolism, sulfur relay system was significantly higher and the proportion of d -arginine and d -ornithine metabolism and flavonoid biosynthesis was significantly lower. In conclusion, we identified differences of the mucosa-associated microbiome between Japanese patients with functional constipation and healthy controls. The mucosa-associated microbiome of functional constipation was characterized by higher levels of Bacteroidetes (Alistipes).